2014
DOI: 10.5334/jbr-btr.741
|View full text |Cite
|
Sign up to set email alerts
|

CT features of small bowel obstruction sur to mesodiverticular band

Abstract: Meckel's diverticulum is the most common congenital anomaly of the small intestine. Common complications related to a Meckel's diverticulum include hemorrhage, intestinal obstruction, and inflammation. Small bowel obstruction due to mesodiverticular band of Meckel's diverticulum is a rare complication. Herein, we report a case of small bowel obstruction occurring due to mesodiverticular band of a Meckel's diverticulum. The important aspect of our case is clear demonstration of the mesodiverticular band adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Imaging features of the mesodiverticular band of the Meckel’s diverticulum have been published. 15 , 16 Sun et al 20 demonstrated the mesodiverticular band as a hyperechoic line in their cases and highlighted the feasibility of high frequency ultrasonography, particularly in children, in revealing congenital bands. However, they emphasized that CT is superior to ultrasonography in detecting the aetiology of small bowel obstruction accurately in adult or obese patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Imaging features of the mesodiverticular band of the Meckel’s diverticulum have been published. 15 , 16 Sun et al 20 demonstrated the mesodiverticular band as a hyperechoic line in their cases and highlighted the feasibility of high frequency ultrasonography, particularly in children, in revealing congenital bands. However, they emphasized that CT is superior to ultrasonography in detecting the aetiology of small bowel obstruction accurately in adult or obese patients.…”
Section: Discussionmentioning
confidence: 98%
“…Intestinal obstruction owing to mesodiverticular band has been reported in patients with Meckel’s diverticulum. 14 16 , 17 , 18 In addition, Vork et al 19 have pointed out the high mortality rate of Meckel’s diverticulum combined with mesodiverticular band and the importance of immediate surgery. In this setting, internal herniation of the small bowel loops underneath the mesodiverticular band is the main mechanism for bowel obstruction, as seen in the presented case.…”
Section: Discussionmentioning
confidence: 99%
“…Meckel diverticulum is a common congenital intestinal malformation caused by embryonic dysplasia. [ 8 ] Small intestinal diverticulum was first described by Hidaus in 1958, but Meckel diverticulum was named by Johann Friedrich Meckel the Younger in 1809 [ 9 ] and identified to be true diverticulum because it usually involves the whole layer of the small bowel. [ 10 ] It was found that in the early stages of embryonic development, the yolk tube is located between the midgut and the yolk sac; subsequently, the yolk tube gradually shrinks into the fiber cord, and then completely degrades without any traces.…”
Section: Discussionmentioning
confidence: 99%
“…CTE can not only show the shape of the diverticulum but can also show the diverticulum cavity and adjacent abnormal structural changes. [ 8 , 35 ] However, the detection is related to the amount of peritoneal fat; thus, CTE should not be used in patients with a high body mass index. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…As the vitellointestinal duct connects the developing midgut to the yolk sac in the embryo, incomplete resorption of the obliterated vitelline duct results in fibrous band connecting the distal ileum to the umbilicus. Although, in the majority, Meckel's diverticulum does not lead to any complications, approximately 4% of the affected individuals develop complications related to Meckel's diverticulum including haemorrhage, perforation, diverticulitis, and obstruction [2]. Double IVC is also a rare presentation and is usually identified incidentally.…”
Section: Introductionmentioning
confidence: 99%